Um estudo sobre a migração de japoneses para a Amazônia peruana e sua continuação para a Amazônia brasileira - SILVA NETO, Francisco Rodrigues da (Universidade Federal do Pará, 2014)
The arrival of Japanese immigrants to Peru, aboard the ship Sakura Maru, in 1899, to work on the farms of the Peruvian coast, coincides with the heydays of rubber exploitation in the Amazon, which made this region attractive to migrants who did not remain in these farms. In the same year of the arrival of the ship Sakura Maru, 91 of these immigrants moved to the current department of Madre de Dios south of the Peruvian Amazon. After the cycle of exploitation of rubber, many Japanese immigrants remained in the Amazon and in Madre de Dios they settled around Puerto Maldonado, emerging a thriving Japanese community that remains up today. At the time of rubber exploitation some Japanese migrated to the current state of Acre (Brazil), called Peru kudari (those that descended from Peru), but few settled, spreading themselves, after the collapse of the rubber economy, to other places of Brazil and other countries. Thus, this thesis aims to demonstrate that migration of Japanese to the department of Madre de Dios in the Peruvian Amazon, and the emergence and consolidation of a Japanese community in Puerto Maldonado (capital of this department), were caused by three main factors: 1 ) a continuous policy in favor of Japanese immigration to Peru during the first decades of the twentieth century aimed to provide labor to the farms of sugar cane and cotton of the coast; 2) Involvement of Japanese immigrants in economic activities during the expansion of rubber exploitation in the Peruvian Amazon; and 3) Strengthening of these activities after the collapse of the rubber economy to ensure the supply of products required for the remaining population, including replacing of products imported or supplied by large companies. These factors were not found among Japanese who moved to Acre (Brazil), thus not getting the setting of Japanese communities that remained until today. The sources used in this study were composed of literature on international migration, data from the Peruvian and Brazilian censuses, newspapers of the time, diplomatic documents, and provincial reports, among others. The thesis is a study of historical demography using quantitative and qualitative data, in the quest to understand the historical process of the research object, in order to explain the developments that occurred in the communities of Japanese immigrants both in Madre de Dios (Peru) and Acre (Brazil).